ULTRASONIC ASSISTED SECONDARY GROWTH OF DECA-DODECASIL 3 RHOMBOHEDRAL (DDR3) MEMBRANE: SYNTHESIS, CHARACTERIZATION AND ITS PERFORMANCE IN C02/CH4 SEPARATION. - , MUHAMMAD MUBASHIR (2015)
Over the last few decades, much research has been done on the removal of CO2 from CH4 especially in natural gas processing. The presence of C02 decreases the heating value of natural gas and caused equipment corrosion in the existence ofwater. Meanwhile, membrane separation technology has received much attention in CO2 separation mainly due to its advantages compared to conventional separation technologies. Among the membrane materials, zeolite membrane which categorized under inorganic membrane type, is preferred in CO2 separation from CH4 over polymeric and mixed matrix membranes attributed to their characteristics including, well define pore structure, molecular sieving property and high CO2 selectivity. Deca-dodecasil 3 Rhombohedral (DDR3) membrane is a type of zeolite membrane which showed the highest CO2/CH4 selectivity up to 670.